The potential of sodium carbonate and Tiron extractions for the determination of silicon contents in plant samples—A method comparison using hydrofluoric acid digestion as reference - Puppe, Daniel; Kaczorek, Danuta; Buhtz, Christian; Schaller, Jörg (Frontiers in Environmental Science, 2023)
For the determination of silicon (Si) contents in plant materials several methods are in use, but as all of these methods exhibit specific advantages and drawbacks, none of them has become prevalent. Alkaline chemicals are widely used to extract Si from plant samples, because this method is comparably simple, fast, and cheap. However, a comprehensive method comparison between different alkaline extractions to different plant organs is still missing, as well as understanding of the relationship between Si content quantified with those methods and soil silicon availability. In our study we performed two different alkaline (sodium carbonate (Na2CO3) and Tiron) extractions to determine Si contents in husk and straw samples of winter wheat (Triticum aestivum). Results obtained from hydrofluoric (HF) acid digestion were used as reference as this method is assumed to completely dissolve Si in a plant material. We evaluated the efficacy of simple, single-step Na2CO3 and Tiron extractions in relation to complex, multistep HF extractions and analyzed the relationships between Si and phytolith contents in plant samples and plant available Si concentrations in corresponding soil samples. Irrespective of the plant material used (husk or straw) we found Tiron to be more efficient in Si extraction compared to Na2CO3. While Na2CO3 extractions systematically underestimated Si contents in the tested plant materials, the results of Tiron extractions were comparable to the results of HF digestions, at least for husk samples. Phytolith contents in plant samples were strongly positively correlated to Si contents obtained from extractions, especially in husk samples. Plant available Si in soil samples was also reflected best in husk Si contents. Based on our results we recommend the use of Tiron for the extraction of Si from plant materials as this method provided more reliable results compared to the Na2CO3 extraction.